SNBT Debriefing for Students of SMA Kanzul Mubarok Bekasi - Sigit Widiyarto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of the SNBT (National Selection Based on Test) will be carried out in 2023, so it is necessary to provide debriefing so that students have a thorough picture and preparation for facing the SNBT later. The purpose of this activity is to introduce and provide SNBT material which will be tested later. This activity was attended by 34 grade 12 students of SMA Kanzul Mubarok, Bekasi. The activity was carried out with 1 face-to-face counseling and 5 face-to-face material deepening and 2 try outs. The material provided includes introduction to SNBT procedures, general reasoning, reading comprehension, general knowledge and understanding, Indonesian language literacy, English literacy and quantitative knowledge. Based on the results, students scored 64 in the first tryout and got 69.9 in the second tryout. Counseling to parents also determines the results of trials that have been carried out by students. The activity needs to be continued by carrying out more challenging practice questions.